Cancer Illness Perception and Self-Management of Chinese Patients - Fang-Yu Chou (Elsevier, 2019)
Objective: The purpose of this article is to examine the relationships of illness perception, self-care, self-efficacy, and self-care strategies and their effects on Chinese cancer patients' quality of life (QOL). Methods: Questionnaires include data on demographic characteristics, illness perception, symptom self-care activity, and QOL. A secondary analysis was conducted on a sample of ethnic Chinese breast-and-colon cancer patients (n = 159) to examine multivariate associations. Descriptive statistics, bivariate correlational analysis, and hierarchical regression analysis were used to analyze quantitative data. Results: The hierarchical regression model explained 43% of variance in QOL. Perceived illness consequence, personal control, and performance functioning status were found to be significant predictors in the model. Comparisons between breast-and-colon cancer patients showed that colon cancer patients significantly perceived higher levels of chronicity and negativity toward cancer than breast cancer patients. Conversely, breast cancer patients had significantly higher level of QOL and efficacy in making decision. Stress and overwork were the common perceived causes of cancer reported by these patients. Conclusions: These findings suggest that improving self-care efficacy and positive personal control can improve Chinese cancer patients' QOL. Variation in illness perceptions of cancer by different types of cancer should be considered in cancer survivorship planning and patient education.